Campo-relação na consulta ginecológica: considerações psicanalíticas a partir da teoria do campos - Peres, Marcia Cristina Terra de Siqueira (2005)
In this study regarding Field-Relation on gynaecological consultation, the purpose was to discover the underlying possible and countless implications behind doctor-patient relationship, in particular, the field of doctor-patient relationship in the gynaecological consultation. To reach this goal I will formulate an hypothesis that such field supports a stressful situation to the laden and loaded doctor of the contemporary world. The subject concernment was taken up from the author s experience between Medicine and Psychoanalysis. The theoretical point of reference adopted by the Field Theory which takes for granted field rupture psychoanalytic method, as unveil of off-stage sense by the routine, allowing the use of Psychoanalysis beyond analytical session and divan. First and foremost, five extract cases are presented, taken from gynecological consultations, as well as some feelings which has been apprehended from them. Some colleagues speeches have been collected at Gynaecological Congress which evoke some questions and they served as inspirations to be adopted by the Investigation Group in Therapeutics Function (GIFT) as an investigation model. Three GIFT groups will be followed now presented by their narrations and discussions done with the gynaecologists. It was found out that the doctor became a patient and their situation needed to be taken into account. Several apprehensions could be done about medical adverse condition submission and that adverse condition interferes negatively on the doctor-patient relationship as well as on the exercise of the therapeutic function. There are many obstacles on the doctor s life that leads to not experience their own emotional experimentation. In their professional formation, they learn to cut their personal life, even without anesthesia, remaining so little time to themselves of human warmth, friendly touch, leisure, delectation, and so on. Maybe, it would be necessary to content with some time of attention, with a charismatic look, a wide smile, a warming touch, with some comforting words and with a patient listening as well.